The Key Principles of a Systematic Approach to Surahs of the Holy Quran From the Perspective of Proponents of Structural Coherence of the Surahs - Fatemeh Khiveh; Abbas Mossalaee Pour; Abdolhadi Feghhi Zadeh; Seyed Ziaeddin Tabei, MD (LECTURES: Journal of Islamic and Education Studies, 2025)
The Quran is an eternal divine miracle with purposeful and coherent verses and chapters. However, themes are distributed throughout the text. Today, orientalists' efforts to present the Quran as scattered and disorganized on the one hand and disagreements among Quranic scholars regarding the coherence of the Quranic surahs on the other have caused the divine book to be exposed to fallacies. In this study, the aim is to examine the principles of discovering the purposes of the surahs of the Holy Quran from the perspective of the two sects. Therefore, the most important principles used by the proponents of the structural coherence theory were analyzed and criticized, including the containment (revelation) of the structure of the surahs; the limitation of the Holy Quran to the word surah; the miracle of the Quran and its relationship with the purposes of the surah. This theory has opened new horizons in the contemplation and interpretation of the Holy Quran and has caused the coherence in a surah to be seen as a whole and as a network. The research method in this article is descriptive-analytical, in that first evidence and data are collected, and then their logical analysis is carried out.